Tumor Microenvironment Remodeling by 4-Methylumbelliferone Boosts the Antitumor Effect of Combined Immunotherapy in Murine Colorectal Carcinoma - Malvicini, Mariana (2015)
We have previously demonstrated that a low dose of cyclophosphamide (Cy) combined with gene therapy of interleukin-12 (AdIL-12) has a synergistic, although limited, antitumoral effect in mice with colorectal carcinoma. The main mechanism involved in the efficacy of Cy+AdIL-12 was the induction of a specific immune response mediated by cytotoxic T lymphocytes. Our current aims were to evaluate the effects of 4-methylumbelliferone (4Mu), a selective inhibitor of hyaluronan (HA) synthesis, on tumor microenvironment (TME) and to investigate how 4Mu affects the therapeutic efficacy of Cy+AdIL-12. The results showed that 4Mu significantly reduced the amount of tumoral HA leading to a significant decrease in tumor interstitial pressure (TIP). As a consequence, tumor perfusion was improved allowing an increased adenoviral transgene expression. In addition, treatment with 4Mu boosted the number of cytotoxic T lymphocytes that reach the tumor after adoptive transfer resulting in a potent inhibition of tumor growth. Importantly, we observed complete tumor regression in 75% of mice when 4Mu was administrated in combination with Cy+AdIL-12. The triple combination 4Mu+Cy+AdIL-12 also induced a shift toward antiangiogenic factors production in tumor milieu. Our results showed that TME remodeling is an interesting strategy to increase the efficacy of anticancer immunotherapies based on gene and/or cell therapy.